The Komodo dragon - Owings, Lisa. (Minneapolis, MN : Bellwether Media, 2012)
Provides information about Komodo dragons, what they look like, where they live, how they eat, and the danger they can pose to humans.
Includes bibliographical references (p. 23) and index.
School Library Journal, February 2012.
School Library Journal.
4.8
3-6
Keywords: Komodo dragon -- Juvenile literature; Komodo dragon; Komodo dragons; Komodo dragon; Lizards; Animals -- Asia